Caspian Sea Route Gains Traction in Changing Regional Dynamics (Global Journal of Human-Social Science, 2023)
imed at boosting connectivity and cargo transportation between Central Asia and South Caucasus Kazakhstan Government on June 23rd 2023 announced establishment of a jointly owned logistics company along with Azerbaijan and Georgia A bilateral agreement was signed during Kazakhstan Prime Minister Alikhan Smailov s visit to Baku with his Azerbaijani counterpart Ali Asadov Georgia is expected to sign the agreement soon The company s primary goal is to transfer freight between China and Europe using the Trans-Caspian International Transport Route TITR which is also called as the Middle Corridor It also aims to reduce transportation tariffs and increase connectivity efficiency by streamlining procedures with digital means This route seeks to reduce delivery time between Chinese territory and Europe from current 18-23 days to 10-15 days 1 A large part of the rail traffic from China and Central Asia to Europe passes through Russia However due to sanctions imposed on Russia following the Ukraine crisis Central Asian and South Caucasian countries seeking for alternative routes The TITR or Middle Corridor is therefore gaining popularity as a key East-West link and holds immense potential to boost economic growth across the regions